Diabetic: A Comparative Study - Dhungel, Alok; Wassem, Tariq; Upadhyay-Dhungel, Kshitiz (Janaki Medical College Journal of Medical Science, 2017)
Background and Objectives: Type II diabetes mellitus (DM) is particularly common medical disorder and is leading cause of morbidity worldwide. The complication of DM is due to micro or macro vascular damage. The presence of an extensive microvascular circulation and abundant connective tissue in the lungs raises the possibility that lung tissue may be a target organ in diabetic patients and thus pulmonary function test can be affected by DM. This study was designed to compare pulmonary function test between Type II diabetic and non-diabetic individuals; and, with the duration of DM. Material and Methods: This cross sectional comparative study was conducted at King Edward Medical University, Lahore Pakistan. Total sample consist of 91 diabetic and 91 non-diabetic grouped as group A and group B. FEV1, FVC, FEV1/FVC ratio, and PEFR were compared within two groups and with the duration of DM. Results: Total 182 sample with mean age 53.1±5.90 years, with 91(50%) male and 91(50%) female. Group A and B had 91(50%) sample each. Mean value of FVC, FEV1 and PEFR showed statistically significant difference among the both group. Mean of FVC decreases significantly with the increasing duration of DM; although, is not significant with FEV1, FEV1/FVC ratio, and PEFR. Conclusion: Diabetic group showed significantly impaired pulmonary functions test as FEV1, FVC, and PEFR as compare to non-diabetic group. Janaki Medical College Journal of Medical Sciences (2016) Vol. 4 (1): 19-26